Knights of Faith: Christian Existentialism in Colin McDougall’s Execution - Abram, Zachary (Studies in Canadian Literature, 2013)
Colin McDougall’s only novel, Execution, is bookended by two senseless executions. The first execution prompts an existential crisis for the characters involved. The second, paradoxically, somehow atones for the first and moral order is restored. McDougall’s allusions to existentialists like Franz Kafka seem to indicate that he wished Execution to be read within the tradition of existential fiction. The novel’s ending, however, which features a proxy crucifixion, complicates this interpretation since novels within that tradition do not typically allow for any kind of spiritual transcendence. Understanding this seemingly irreconcilable tension means eschewing the dominant form of mid-century existentialism characterized by Jean-Paul Sartre and Albert Camus in favour of one of existentialism’s foundational figures. A close reading of Execution, considering the formative texts of existentialism and a comparative reading of works by its international influences, reveals a valuable theoretical matrix for parsing the difficult philosophy of this neglected novel. For Execution accords with an earlier form of existentialism, one that predates the school’s consensus atheism and is articulated primarily by Søren Kierkegaard in Fear and Trembling.